THE POLITICS OF ISLAMIC LEADERSHIP AND REPRESENTATION IN NIGERIA: A HISTORICAL ANALYTICAL STUDY ON THE NIGERIAN SUPREME COUNCIL FOR ISLAMIC AFFAIRS (NSCIA) - Rufai’, Saheed Ahmad (Journal of Al-Tamaddun, 2013)
Nigeria is a leading African country with a Muslim majority population. Yet Nigerian Muslims, since the spread of Islam to the country in the thirteenth century, had continued to operate in disarray and were never known to have spoken in one voice until the founding of the Nigerian Supreme Council for Islamic Affairs (NSCIA) in 1973. This paper traces the origins of the Nigerian Muslims? quest for a united front and articulates the factors that informed their clamour for such a platform. The paper enumerates the early initiatives of the Council and its attitudes to various political crises in the country especially that which ensued after the annulment by former President Ibrahim Babangida of the June 12, 1993 presidential elections widely believed to have been overwhelmingly won by a Vice President-General of the Council, Alhaji Moshood Abiola. The paper relies more on primary sources and oral information formally collected from a number of individuals who were not only eye witnesses but also dramatic personae in the politics of Islamic leadership in contemporary Nigeria, owing to the dearth of sophisticated scholarship on the subject. So far, references to the effects of leadership crises on Islamic leadership in the country, have been broad, loose and general so much that they can hardly be related to a particular political experience or put in a specific perspective. The paper employs a philosophical method in its historical analysis and concludes by evaluating the activities of the Council and concluding that it is fast becoming moribund.